Microstructural buckling in soft visco-hyperelastic laminates - Lapina, Tatiana; Xiang, Yuhai; Yao, Qi; Chen, Dean; Li, Jian; Steinmann, Paul; Rudykh, Stephan (International Journal of Solids and Structures, 2025)
In this work, we study the role of visco-(hyper)elasticity in the microstructural buckling of soft laminates under compressive loads. We find that the onset of buckling is related to the contrast in specific stress components; this allows us to develop analytical estimates for the critical loading. Our numerical analysis provides details on the dependence of critical strain and wavelength on the loading strain rate. We show that by activating the viscoelasticity of the stiffer layer with an increasing strain rate, one can promote the early development of the buckling (the critical strain decreases as the strain rate is increased). The tunability of the critical strain is bounded by the limits for fast and slow loading rates. Furthermore, the buckling wavelength can be tuned through strain rate variability; this effect is stronger in laminates with lower volume fractions (of stiff layer phase), while for high volume fractions, laminates tend to develop longer wavelength instabilities with diminishing tunability.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Buckling; Critical strain; Critical wavenumber; Laminates; Viscoelasticity